IDENTIFIKASI SUMBER PENCEMAR DAN ANALISIS KUALITAS AIR TUKAD YEH SUNGI DI KABUPATEN TABANAN DENGAN METODE INDEKS PENCEMARAN - Ni Made Setiari; M.S. Mahendra; I Wayan Budiarsa Suyasa (Master Program of Environmental Science, Postgraduate Program of Udayana University, 2012)
Based on the data of Environmental Status of Bali Province Year 2009, Sungi River is the one of ten rivers that have experience quality degradation which contaminated by waste. Pollution parameters that have exc.eeded the quality standard, are: BOD, COD, Total Phosphate, Total Coliform, and Faecal Coliform. It requires to concerned because Sungi River as the point area for drinking water in Tabanan (data of Environmental Board of Bali Province). Purpose of research is to determine the characteristic of pollution source which will be impact to the changing of water quality in physical, chemical, and biological in middle and down stream area, detern1ine the pollution index in up stream, middle. and dow stream area of Sungi River. Water parameters that will observe are: temperature, pH, turbidity, TDS, TSS, DHL, DO, BOD, COD, Total Phosphate, Total Coliform and Faecal Coliform. The measurement result will compare with the best of water quality, based on the Regulation of Bali Governor Number 8 Year 2007, because of it utilization as drinking water. Result of research shown that the activity in Sungi River dominated by agriculture activity, settlement, animal husbandry, and industry that located in dov.n stream area. The waste that result from the above activities caused the degradation of water quality that shown by the increasing of water parameter indicators, such as: BOD, COD, Total Phosphate, and Faecal Coliform Bacteria. In the middle will increasing and down stream area will get degradation. This condition is inversely proportional to the content of DO as impact of contaminants accumulation, such as: organic waste in middle are, because the water movement is more calm with average water flow is 0,14 m/second compared with the up and down stream area with average water flow are 0,15 m/second and 0,35 m/second. Characteristic of pollution source which effect the water quality at Sungi River in area I caused by llie activities of agriculture, animal husbandry, settlement, and industry, for area II caused by the activities of agriculture, animal husbandry, settlement, and villa. The quality staLus of Sungi Rlver in up stream area still result a good quality water but in the middle and down stream area are get lightly pollution. Water quality parameter which exceeded a good water quality in Sw1gi Rive,· is Total Phosphate with average value is 0,44 mg/I in the middle area, 0,40 mg/l in down stream area and Faecal Coliform with average value is 166/100 ml in the middle area and 152/100 ml in the down stream area.